A mental health framework from the voices of refugees. (December 2022) - Kanagaratnam, Pushpa; Pandalangat, Nalini; Silver, Ivan; Toner, Brenda
Background: Refugee groups fleeing war and violence and resettling in the West are one of the population groups that are poorly understood. Understanding their mental health challenges and providing effective and evidence-based interventions continue to be formidable challenges. Aim: This study presents a refugee mental health framework [RMHF] that was developed to address the gaps in understanding and responding to the needs of refugee populations by prioritizing their voices, and incorporating lessons learned from working with these refugee communities into the development of the framework. Method: A RMHF was developed, presented and refined with input from refugee communities, multiple stakeholders and an expert panel. Results/conclusions: This paper presents the process and finalized framework, and discusses its utility as a mapping, planning and intervention tool in supporting refugee communities with their resettlement and promoting mental wellbeing.